The digital humanities : a primer for students and scholars - Gardiner, Eileen; Musto, Ronald G. (New York, NY : Cambridge University Press, 2015)
'The Digital Humanities is a comprehensive introduction and practical guide to how humanists use the digital to conduct research, organize materials, analyze, and publish findings. It summarizes the turn toward the digital that is reinventing every aspect of the humanities among scholars, libraries, publishers, administrators, and the public. Beginning with some definitions and a brief historical survey of the humanities, the book examines how humanists work, what they study, and how humanists and their research have been impacted by the digital and how, in turn, they shape it. It surveys digital humanities tools and their functions, the digital humanists' environments, and the outcomes and reception of their work. The book pays particular attention to both theoretical underpinnings and practical considerations for embarking on digital humanities projects. It places the digital humanities firmly within the historical traditions of the humanities and in the contexts of current academic and scholarly life'--
1. Introduction to the digital humanities -- 2. The organization of humanities research -- 3. The elements of digital humanities : text and document -- 4. The elements of digital humanities : object, artifact, image, sound, space -- 5. Digital tools -- 6. Digital environments -- 7. Publication : pre-release, release, and beyond -- 8. The meta-issues of digital humanities 1 -- Meta-issues 2 : copyright and other rights, DRM, open access -- 10. The evolving landscape for the digital humanities -- Epilogue: The half-life of wisdom -- Appendix: Digital tools.
Includes bibliographical references (pages 253-259) and index.
Keywords: Digital humanities; Humanities -- Research; Humanities -- Methodology; Humanities -- Study and teaching; Humanists -- Intellectual life; Digital media; Digital communications; Information storage and retrieval systems -- Humanities